Análisis a los Estados Financieros al Autoservicio Gamahorro del cantón Catamayo en los períodos 2020 y 2021 - Robalino Riofrio, Yessica Nayeli (2023)
The Curricular Integration Work entitled "Analysis of the Financial Statements of the Gamahorro Self-service of the Catamayo canton in the periods 2020 and 2021", allows to comply with the objectives set out in the Curricular Integration Work by carrying out the Vertical, Horizontal Analysis and the application of Financial Indicators, in order to determine the economic situation, Liquidity, Profitability, Indebtedness and Activity, of the Gamahorro Self-Service; In addition, to comply with the essential requirement of obtaining the title of License in Accounting and Auditing. The Vertical Analysis was carried out, evidencing that the most relevant account within the Statement of Financial Position was the Current Assets account with 66.16% in 2020 and 71.51% in 2021, reflected especially in Accounts Receivable. with a value of $188,906.78, which represents 27.68% in the year 2020 and in the year 2021 a value of $265,413.42, equivalent to 34.33%, determining that the Self-service Gamahorro has an increase due to lack of cancellation of debts that it maintains by its clients; In the Merchandise Inventory account in the year 2020 a value of $171,037.98 was obtained, which represents 25.06% and in the year 2021 a value of $203,296.61, which is equivalent to 26.29%, this increase is the result that represents the activity carried out, such as the purchase and sale of essential products that the company has. Regarding the application of the Horizontal Analysis in the Income Statement, it was observed that the Income account in the year 2021 sold the amount of $881,440.47, while in the year 2020 $811,374.19 was sold, with a difference of $69,309, $07, which represents 8.31%; while the group of Costs for the year 2020 represents a value of $679,350.25 and for the year 2021 amounted to $781,867.48, there being a difference between the two periods of $102,506.23 value that is consistent with the year 2021 in this period the entity increased its product sales; The total group of Expenses in the year 2020 is $38,960.21 and for the year 2021 of $73,238.81, a difference of $34,275.60 is marked, which represents an 87.97% increase in the total Expense in the year 2021 representing an increase from one year to the next, this is due to the economic activity that the commercial presented due to hiring personnel due to the increase in all operating expenses. 5 Regarding the application of Financial Indicators, the entity has an appropriate level of Liquidity to cover acquired debts, the level of Inventory Rotation in the year 2020 has rotated 3.97 times, that is to say that the merchandise remained in the warehouse for 92 days while the year 2021 has rotated 3.85 times, but increased to 95 days, based on the results obtained, the company presents the same result in the two years analyzed, thus, it does not have an adequate rotation of inventories, thus that the merchandise remains in stock for a long time since it is not profitable to keep the products in the warehouse for a long time during a month; Regarding the indebtedness of the company, for the year 2020 it is $0.24 cents and for the year 2021 it is $0.15 cents, in both periods a low index is maintained, that is, it does not require external financing since it can finance all its activities with its own resources; In the Profitability Indicator it was possible to observe that in 2020 the gross profit margin is 16.27% and in 2021 it is 11.30% on net sales, which indicates that in 2020 there was an increase of 4 .97% this due to the acquisition of merchandise at an almost stable cost that is beneficial for the salesperson because with this it led him to obtain an increase in his profit margin. Finally, the report was prepared that details the shortcomings found, conclusions and recommendations, which will allow you to improve business development, financial and economic administration that facilitate correct decision making.